A study on effectiveness of inventory control at Start Mart Caltex station / Ahmad Surani Zainal Abidin - Zainal Abidin, Ahmad Surani (1998)
There are a lot of factors that contributed to the ineffective of inventory control. From this research, we will look into factors that contributed to the ineffective inventory control at Star Mart Caltex Station. From the observation made at most of the Star Mart in Klang Vally, 4 major problems had been identified that caused to the problem which is less knowledge, promotion done, the usage of computerized system and the relationship with suppliers.